Electronic structure and optical properties of Ag-MoS2 composite systems. (2nd February 2018) - Yang, Hongchao; Wei, Wei; Mu, Cong; Sun, Qilong; Huang, Baibiao; Dai, Ying
Abstract: It is important to study the adsorption properties of single Ag atom and Ag clusters on monolayer MoS2 as well as the energy transfer mechanism, in order to understand the stability and the high photocatalytic activity of Ag-MoS2 composite systems. It has been confirmed that Ag nanoparticles on monolayer MoS2 are presented as active reduction and oxidation sites, playing a role in mediating charge transfer from electron-rich MoS2 to target species. It is of interest that the band structure changes little upon Ag nanoparticle adsorption, although impurity states between bulk VBM and CBM do appear. In comparison to bare single-layer MoS2, as a result, the intensity of light absorption can be enhanced and the range of light absorption can be extended to the near infrared region. It is found that the reduction ability could be improved due to Ag nanoparticle adsorption. The present study may be useful for developing 2D materials with single metal atoms or metal nanoparticles deposited for photocatalysis.